Protection from stored grain insects using transgenic maize hybrids and implications for Aspergillus flavus and aflatoxin contamination - Julie Aiza L. Mandap; Richard L. Hellmich; Mark Busman; Dirk E. Maier; Gary P. Munkvold (Journal of Stored Products Research, 2024)

Reducing production of fumonisin mycotoxins in Fusarium verticillioides by RNA interference - Eric T. Johnson; Robert H. Proctor; Christopher A. Dunlap; Mark Busman (Mycotoxin Research, 2018)

Quantification of patulin in fruit leathers by ultra-high-performance liquid chromatography-photodiode array (UPLC-PDA) - Chris M. Maragos; Mark Busman; Liang Ma; John Bobell (Food Additives & Contaminants: Part A, 2015)

Determination of the aflatoxin AFB1 from corn by direct analysis in real time-mass spectrometry (DART-MS) - Mark Busman; Jihong Liu; Hongjian Zhong; John R. Bobell; Chris M. Maragos (Food Additives & Contaminants: Part A, 2014)

Domoic acid production near California coastal upwelling zones, June 1998 - Vera L. Trainer; Nicolaus G. Adams; Brian D. Bill; Carla M. Stehr; John C. Wekell; Peter Moeller; Mark Busman; Dana Woodruff (Limnology and Oceanography, 2000)
Sea lion mortalities in central California during May and June 1998 were traced to their ingestion of sardines and anchovies that had accumulated the neurotoxin domoic acid. The detection of toxin in urine, feces, and stomach contents of several sea lions represents the first proven occurrence of domoic acid transfer through the food chain to a marine mammal. The pennate diatoms, Pseudo‐nitzschia multiseries and P. australis , were the dominant, toxin‐producing phytoplankton constituting algal blooms near Monterey Bay, Half Moon Bay, and Oceano Dunes, areas where sea lions with neurological symptoms stranded. Toxic Pseudo‐nitzschia were also found near Morro Bay Point Conception, Point Arguello, and Santa Barbara, demonstrating that these specie were widespread along the central California coast in June 1998. Measurements of domoic acid during three cruises in early June showed the highest cellular toxin levels in P. multiseries near Point A~o Nuevo at 6 pg cell −1 and in P. australis from Morro Bay at 78 pg cell −1 . Maximum cellular domoic acid levels were observed within 20 km of the coast between 0 and 5 m depth, although toxin was also measured t depths of 40 m. Hydrographic data indicated that the highest toxin levels and greatest numbers of toxic cells were positioned in water masses associated with upwelling zones near coastal headlands. Nutrient levels at these sites were less than those typically measured during periods of active upwelling, due to the 1998 El Ni~o event. The flow of cells and/or nutrients from coastal headlands into embayments wher cells can multiply in a stratified environment is a possible mechanism of bloom development along the central California coast. This coupling of toxic Pseudo‐nitzschia growth near upwelling zones with physical processes involved in cell transport will be understood only when long‐term measurements are made at several key coastal locations, aiding in our capability to predict domoic‐acid producing algal blooms.